ARGUMENT. MISFORMING UNIQUENESS - CÂMPEAN, Noemina; CÂMPEAN, Flaviu (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
Searching for a theme of the conference, we kept stumbling on the problem of the status of the individual, which seems to have been either lost along the way, or absorbed by more strenuous philosophical inquiries, pertaining to the eternal quest of linking the Universal to the Particular, the singular to plurality. Both Metaphysics and Late Modern Thought reinvented their philosophical or sometimes anti-philosophical bases, seeming to actually hold back on the ineffable actuality of the living individual. Still, Philosophy is always bordering on a real that cannot be represented or positively signified, but is effective as such and philosophers have coined different concepts in order to grasp its negativity, like Kierkegaard’s unique – den Enkelte, Heidegger’s Dasein or maybe even Derrida’s différance, to name only these. But the option of our philosophical discourse was rather for forms, as well as that of Modern science and Epistemology that developed as a bundle of theories about/ of forms. And they are still doing it to some extent, as even nowadays science finds it hard to unleash from the forms that have guided and recreated it.